O direito à educação infantil em Uberlândia: análise das estratégias do Plano Municipal de Educação (2015 – 2025) - Alves, Laís Hilário (2021)
The present study, in the research line on State, Policy and Education Management, aims to analyze the Education Plan in the municipality of Uberlândia-MG and its interface with the National Education Plan with regard to early childhood education and the proposed goals and strategies which aimed to guarantee and make the right to education at this stage of basic education effective. and the specific goals are: a) analyze and understand how the right to education was constituted in Brazil, based on its conceptualization, historical and legal trajectory; b) analyze educational policies in Brazil and the issue of the right to early childhood education; c) identify and analyze how the right to early childhood education presents itself in educational plans after the Federal Constitution; d) apprehend and analyze the goals and strategies proposed in the Education Plan in the municipality of Uberlândia and their consequences for the realization of the right to early childhood education in the municipality. A qualitative approach was used in this study and bibliographical and documentary research as procedures. In the bibliographical research we take into account the main authors who deal with the Right to Education and Education Plans. The following documents were our documental source: the Brazilian Federal Constitutions; the Law of Directives and Bases of Education (nº 9394/96); the National Education Plan (nº 13.005/2014); the Education Plan in the municipality of Uberlândia (12,209/2015); Municipal Decrees; Municipal Secretariat of Education Reference Document; minutes of meetings; the 2016, 2018 and 2020 National Education Plan monitoring reports; as well as the 2017 and 2019 monitoring reports of the Education Plans in the municipality of Uberlândia. The data reveal that from a legal point of view, the right to education has been improving in Brazil, as well as the guarantee of the right to early childhood education, which advanced in the preparation of legal provisions, but which encountered limits and challenges regarding the implementation of adequate public financing to the detriment of other stages of basic education. As for the goals and strategies of the Education Plan in the municipality of Uberlândia (2015-2025) referring to this stage of education, we can say that some strategies were implemented; however, the goals were not fully met. The municipality does not have a Municipal Education System yet, failing to comply Goal 1 on the promotion, expansion and promotion of early childhood education; it universalized pre-school and expanded the offer of places in day care centers, contributing to the achievement of the goals proposed in the National Education Plan. However, there is a great role of Civil Society Organisations ( CSOs) in this expansion of vacancies, transferring management, organization, pedagogical work, public resources to the private sector, which maintains political and ideological control, removing institutions from public control. Education continues to be transformed into merchandise, distancing itself from public, free, secular and quality education. Education in a literate society is considered an indispensable social right. However, the fight for this right, to keep it and ensure its effectiveness must be constant, not allowing it to be a 'dead letter' in documents.